HASIL EMPAT VARIETAS BAWANG MERAH DENGAN APLIKASI PUPUK HAYATI MIKORIZA DI DESA SETELUK KECAMATAN BATULAYAR KABUPATEN LOMBOK BARAT [YIELD OF FOUR UNION VARIETIES WITH APPLICATIONS OF MYCORRHIZA FERTILIZER IN SETELUK VILLAGE BATULAYAR DISTRICT, WEST LOMBOK] - Wahyu Astiko; I Made Sudantha; Mery Windarningsih; Irwan Muthahanas (Jurnal Sinergitas PKM & CSR, 2018)
Many ways can be done in an effort to increase the production of shallots, such as regulating the right dosage of fertilization, regulating the optimum spacing, proper irrigation, good pest, and disease control and choosing varieties that have high production potential. There are several varieties that are often cultivated by farmers in West Nusa Tenggara, namely Keta Monca varieties from Bima, Brebes varieties originating from Central Java, Super Filip varieties and Vietnamese varieties. Technological innovations by trying out several superior varieties of shallots also need to be socialized to the community by conducting community service activities in an effort to implement a culture system that is environmentally friendly, sustainable and can improve crop yields. This community service activity was carried out in Seteluk Village, Batulayar District, West Lombok Regency, which is a shallot producing area. The method used in carrying out community service is a training method that is continued with practical work in the field by conducting demonstrations and active participatory action research. To see the results of community service an evaluation was conducted which included: average plant height, tuber yield per plot, attendance and participation of participants in adopting the applied technology, and discussion during the extension. The results of the demonstration plot of mycorrhizal biofertilizer application on four shallot varieties showed that the Keta Monca variety originating from Bima gave the best growth and yield and was suitable for planting in the lowlands. The presence and participation of farmers during community service was very enthusiastic about the delivery of extension materials. The participants' understanding of the material provided was very good, as seen from the number of participants who asked questions and the relevance of the questions posed by the participants in accordance with the extension material delivered.